Innovative View on Duration of Working Hours in Russia under Modern Conditions ("Journal "U". Economy. Management. Finance.", 2016)
Objective of this research is the analysis of various options of duration of working hours, developed because of world economy development and personnel policy.
Keywords: changing of duration of working hours; six-hour working day